Developing an Instrument to Assess Teaching Skills of Lab Instructors in Medical Education: Initial Validation - Ahsin, Sadia; Iqbal, Muhammad; Ashraf, Hira (Pakistan Armed Forces Medical Journal, 2025)
Objective: To devise and validate a direct observation tool for assessing lab teaching skills of laboratory instructors namely ‘Direct Observation of Teaching Skills’ (DOTS)Study Design: Mixed method studyPlace and Duration of Study: Foundation University Islamabad and Shifa Tameer-e-Milat University Islamabad, Pakistan from Apr 2021 to Apr 2022.Methodology: More than three hundred and fifty qualified medical educationists who were registered with Pakistan Medical and Dental Council and having five years and above teaching experience participated through purposive sampling. Tool development was done in systematic seven recommended steps of AMEE Guide 87 including 1) Literature Search, 2) Focus group discussion, n= 7, 3) Synthesis of literature review and focus group discussions, 4) Item development, 5) Expert Validation, 6) Cognitive pretesting n= 5 and 7) Pilot testing n= 310. SPSS and AMOS were used for data analysis.Results: A 29-item tool evaluating laboratory teacher performance including laboratory instructions, activities and management was validated for content, response process and construct with Scale Content Validity Index/ Average (S-CVI) of 0.867 and S-CVI Universal agreement of 0.989. Confirmatory analysis showed factor loading of > 0.50 for all items. The absolute fit value of Observed normed χ2 was 2.99, goodness of fit index was 0.79 and root mean square error of approximation was 0.08. Internal consistency for lab instruction, lab activities and lab management showed Cronbach’s α values of 0.909, 0.899, 0.912 respectively.Conclusion: The devised tool, DOTS appears reliable and valid in content, response process and construct.